HOW QUIET QUITTING UNDERMINES INNOVATION: MEDIATING EFFECTS OF KNOWLEDGE HOARDING AND PROCRASTINATION AMONG SALESPERSONS IN INDONESIA - Helmy, Irfan; Setyawati, Harini Abrilia (Sosiohumaniora, 2024)
The increasing competition in digital financial services challenges salespersons in traditional microfinance institutions (MFIs) to adopt innovative strategies for survival. This intense pressure has contributed to the growing trend of quiet quitting behavior among salespersons. This research aims to investigate the impact of quiet quitting on innovative work behavior (IWB), with knowledge hoarding and work procrastination as mediating variables. Data were collected through a survey of 557 MFI employees across five districts in Central Java, Indonesia. This study used Smart PLS 4 to examine the proposed hypotheses. The results demonstrate that quiet quitting negatively relates to salespersons’ innovative work behavior. Quiet quitting also has a positive effect on knowledge hoarding and work procrastination, both of which negatively impact innovative work behavior. In addition, based on the evaluation of indirect effects, this study reveals that the association between quiet quitting and innovative work behavior is mediated by knowledge hoarding and work procrastination. This research addresses an important gap in the literature by investigating the influence of quiet quitting on innovative work behavior. Although scholars have investigated both constructs independently, their direct empirical linkage remains insufficiently explored within previous studies. By incorporating knowledge hoarding and work procrastination as mediating variables, this study develops a more comprehensive model to understand the mechanisms through which quiet quitting impacts employees’ innovation. The findings also provide valuable insights for MFI managers to address quiet quitting and foster a more innovative sales workforce.